Application of a novel phage ZPAH7 for controlling multidrug-resistant Aeromonas hydrophila on lettuce and reducing biofilms. (April 2021) - Islam, Md. Sharifull; Yang, Xiangwei; Euler, Chad W.; Han, Xueqing; Liu, Jiahui; Hossen, Md. Isrfil; Zhou, Yang; Li, Jinquan
Abstract: Aeromonas hydrophila is an important pathogenic bacterium that causes foodborne illness worldwide. In this study, virulent phages from the sediment of a fish farm were propagated and isolated on a multidrug-resistant strain of A. hydrophila, ZYAH75. One phage, designated as ZPAH7, featured a unique turbid halo around a clear plaque on the bacterial lawn (indicative of potential depolymerase activity), and was selected for further analysis. ZPAH7 was classified as podophage by morphological and genomic methods. Further comparisons of genome nucleotide similarity, ratios of homologous proteins and phylogenetic relatedness among the terminase large subunit and major capsid proteins of similar phage deposited in GENBANK, led us to propose a new genus, ZPAH7virus, in the Autographivirinae subfamily of Podoviridae. ZPAH7 had an adsorption rate of 79% in 5 min, an eclipse period of 15 min, a latent period of 25 min, and a burst size of 148 ± 9 PFU/cell. Antimicrobial application experiments showed that ZPAH7 lead to significantly reduction on A. hydrophila on lettuce. Additionally, ZPAH7 was able to inhibit biofilm formation, as well as degrade and kill bacteria in established biofilms. Furthermore, lytic activity of ZPAH7 remained stable across a wide range of temperatures and pH measurements. These results suggest ZPAH7 could be used as a potential biological control agent against A. hydrophila on food and/or biofilms on food contact surfaces. Highlights: The novel Aeromonas phage (ZPAH7) producing halo on the bacterial lawn was successfully screened out and firstly reported. As a promising food safety biocontrol agent, ZPAH7 presented a wide range of pH tolerance and thermal stability. The new genus ZPAH7virus in Autographivirinae subfamily of Podoviridae was established . ZPAH7 was proved to be effective against biofilm, and can be applied on food matrices or food contact surfaces.